Manual de identidad visual y estrategia de marketing digital para la marca intrépidos 4x4 - Ojeda Flores-Araoz, Tania (2022)
Intrépidos 4x4 is a company dedicated to creating off-road routes through Peru for lovers of 4x4 trucks, better known as all-terrain, and who want to experience the adrenaline in this type of journey outside the city. Although the brand has a presence on digital platforms such as Facebook, Instagram and TikTok, the purpose of this professional work is to propose a digital marketing strategy to increase its reach and the number of subscribers to its routes. In addition, position it as an off-roader community characterized by safety and camaraderie. Based on the analysis of the Intrépidos 4x4 brand, a brand manual was also developed that contains visual identity elements such as a logo, structure for stories and publications, appropriate fonts, photographic style, tone of communication and personality, among others. others. These materials will make it possible to build a consistent brand on all the platforms on which it has a presence and the actions it executes